2012
DOI: 10.1111/j.1469-185x.2012.00221.x
|View full text |Cite
|
Sign up to set email alerts
|

On the evolution of morphogenetic models: mechano‐chemical interactions and an integrated view of cell differentiation, growth, pattern formation and morphogenesis

Abstract: In the 1950s, embryology was conceptualized as four relatively independent problems: cell differentiation, growth, pattern formation and morphogenesis. The mechanisms underlying the first three traditionally have been viewed as being chemical in nature, whereas those underlying morphogenesis have usually been discussed in terms of mechanics. Often, morphogenesis and its mechanical processes have been regarded as subordinate to chemical ones. However, a growing body of evidence indicates that the biomechanics o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
29
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 203 publications
(253 reference statements)
0
29
0
Order By: Relevance
“…This type of patterning mechanism, requiring the active directional transport of an instructive chemical signal and the mechanical changes it induces, both invokes historical ideas and inspires future directions; indeed, further exploration of mechano-chemical regulatory loops in developmental biology will likely provide a rich landscape of interdisciplinary hypotheses [4], [5], [60].…”
Section: Biological Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This type of patterning mechanism, requiring the active directional transport of an instructive chemical signal and the mechanical changes it induces, both invokes historical ideas and inspires future directions; indeed, further exploration of mechano-chemical regulatory loops in developmental biology will likely provide a rich landscape of interdisciplinary hypotheses [4], [5], [60].…”
Section: Biological Discussionmentioning
confidence: 99%
“…As exemplified by the seminal work of Alan Turing [1], scientists of diverse disciplines have all attempted to explain biological patterns within their own frameworks [2]. Within the field of developmental biology, these disciplines have been interacting more and more to provide richer details for patterning mechanisms, a trend which will surely continue [3], [4], [5]. One of the most riveting proposals of Turing is that models explaining morphogenesis should consist of 'two parts, the mechanical and the chemical' [1], [4]; using this simple statement as a starting point, we have undertaken to examine how a chemical signal, it's chemical responses, and it's mechanical outputs combine in plant patterning to provide a mechano-chemical regulatory loop.…”
Section: Introductionmentioning
confidence: 99%
“…Since the discovery of embryonic induction, which revealed that secreted molecules are capable of instructing and organizing cells in surrounding tissues (Waddington 1940;Spemann and Mangold 2001), cell-cell signaling has become a sine qua non mechanism of pattern formation in many (if not most) developmental systems (Meyerowitz 2002;Rogers and Schier 2011;Urdy 2012;Kicheva and Briscoe 2015). Experimental manipulations of extracellular signals can impact tissue patterning at a distance (Salazar-Ciudad 2006;Nahmad Bensusan 2011;Perrimon et al 2012;Urdy et al 2016).…”
mentioning
confidence: 99%
“…The first type belongs to the class of lateral inhibition models and the second type belongs to the class of mechanical models. The similarities and differences between these two classes of models-as well as their historical roots-are discussed at length in Urdy (2012), using various examples from developmental biology.…”
Section: Shell Ornamentation and Pigmentationmentioning
confidence: 99%